(untitled) (Economic and Political Thought, 2014)
The main aim of this paper is to engage in a problem of unclear outcomes of empirical research on business cycle synchronization. In order to achieve that, the author presents a model of two economies, which provides very clear tips on shock transmission mechanisms and necessary control variables for the need of econometric evaluation. The presented model shows that the impact of international trade transmission channel, approximated by marginal propensity to consumption, is positive, but exhibits diminishing influence of business cycle synchronization. This conclusion was reached earlier by Silvestre, Mendonça and Passos (2007), and confirmed by the author with the use of nonparametric methods. The model of two countries has also proved that while analysing business cycle synchronization, control is necessary because of the symmetry of shocks distribution, fiscal policy correlation and exchange rate regime. Empirical verification with the use of parametrical methods revealed correctness of the statements, as well as the necessity of control due to monetary policy correlation. On this basis, the author was able to explain the results reached by Baxter and Kouparitsas (2004), as well as Böwer i Guillemineau (2006).